2015
DOI: 10.1177/1934578x1501001138
|View full text |Cite
|
Sign up to set email alerts
|

A New Isoflavone Apioglucoside from the Roots of Dalbergia spinosa

Abstract: Targeting the discovery of novel natural products, the roots of Dalbergia spinosa Roxb has yielded a new isoflavone apioglycoside, 5-hydroxy-6-methoxy-3′,4′-methylenedioxy-7-[(6- O-β-D-apiofuranosyl-β-D-glucopyranosyl) oxy]isoflavone (dalspinin-7- O-β-D-[apiofuranosyl (1→6)] glucopyranoside) (1), together with the known isoflavones, dalspinin (2), dalspinosin (3) and caviunin (4). Their structures were elucidated on the basis of extensive spectral and chemical evidence. To the best of our knowledge, this is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Dalspinin‐7‐ O ‐ β ‐ d ‐galactopyranoside is a glycosylated isoflavone identified in R. canina fruits at 489 m/z. Therefore, the fragment corresponding to the loss of a hexosyl (galactose = −162 uma) gives a dalspinin aglycone at 327 m/z (Table 2), (Radha, Vasantha, & Pitchumani, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Dalspinin‐7‐ O ‐ β ‐ d ‐galactopyranoside is a glycosylated isoflavone identified in R. canina fruits at 489 m/z. Therefore, the fragment corresponding to the loss of a hexosyl (galactose = −162 uma) gives a dalspinin aglycone at 327 m/z (Table 2), (Radha, Vasantha, & Pitchumani, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Kurz, et al, (1881) [22] reported that a spoonful of root powder in a glass of water is sufficient to destroy the effects of alcohol within half an hour even in cases bordering on delirium tremens. Phyto-chemically, several isoflavone compounds such as dalspinin, dalspinosin, caviunin and 5-hydroxy-6-methoxy-3',4'-methylenedioxy-7-[(6-O-β-Dapiofuranosyl-β-D-glucopyranosyl)oxy] isoflavone (dalspinin-7-O-β-D-[apiofuranosy (1->6)] gluco pyranoside), prunetin-4-O-β-D-galactoside, dalspinosin-7-O-β-glucopyranoside were reported from root (Gandidasan, et al, 1998;Radha, et al, 2015) [7,8,30] . Several biological activities on root extracts were reported such as analgesic, anti-inflammatory, antimicrobial, anti-nociceptive, antioxidant, cytotoxicity, cardio vascular effects, diuretic, hypoglycemic, hypothermic, semen coagulant and spermicidal activities (Dhawan, et al, 1977;Senthamarai, et al, 2003;Jaiganesh, et al, 2009a & b;Jaiganesh, et al, 2010;Bala, et al, 2011) [4,2,11,12,13,32] .…”
Section: Introductionmentioning
confidence: 99%